Restorative Justice In Handling Cases Of Children As Perpetrators Of Criminal Acts - Alexander Hutagalung (International Asia Of Law and Money Laundering, 2022)
This writing aims to see and understand about the perpetrators of crimes or criminal acts that can be convicted. Then also want to see how important it is regarding a child who commits a crime or a criminal offense is solved through jusrtice restorative approach. The normative juridical research method through the approach of library studies by collecting secondary data. After the data is collected, the data is processed and analyzed so that conclusions can be drawn from the questions posed in the formulation of the problem. The results showed that those included in the perpetrators of criminal acts are those who do, instruct, advocate and participate. Besides, there are also those who give promises, opportunities, facilities and information. In terms of the importance of a child committing a crime or criminal act being resolved through jusrtice's restorative approach, this is the best alternative that can be done. With this concept, it is expected that all parties can jointly solve the problem by involving victims, perpetrators, including families.